Combinatorial effect of Photorhabdus luminescens TT01 and Bacillus thuringiensis Vip3Aa16 toxin against Agrotis segetum. (February 2018) - Jallouli, Wafa; Boukedi, Hanen; Sellami, Sameh; Frikha, Fakher; Abdelkefi-Mesrati, Lobna; Tounsi, Slim
Abstract: The entomopathogenic Photorhabdus luminescens TT01 is a promoting bacterium that controls effectively many insect pests. Indeed, it exhibited a mortality rate of 32.36% against the first instar larvae of the turnip moth Agrotis segetum, when it was used at a concentration of 5 × 10 7  cells/ml but no toxicity against the second instar larvae in the same condition. P. luminescens TT01 oral toxicity is associated to septicaemia since cells fraction exhibited the highest mortality rate of 34%. In order to enhance P. luminescens TT01 insecticidal potential, combination with Bacillus thuringiensis Vip3Aa16 toxin was tested. An improvement of insecticidal activity was shown. Indeed, 100% mortality of A. segetum first instar larvae was obtained after 2 days of treatment, when using TT01 cells and Vip3Aa16 toxin at a concentration of 5 × 10 7  cells/ml and 9.025 ng/cm 2, respectively. Moreover, growth inhibition rate of 45% of the second instar larvae was observed, when using the same combination. A. segetum mortality could be the result of several alterations in the midgut epithelium caused by Vip3Aa16 toxin, allowing a rapid invasion of the hemocoel by TT01 cells as demonstrated by histopathological study. Clear symptoms of intoxication were observed for all combinations tested, including swelling, vesicle formation, cytoplasm vacuolization and brush border membrane lysis. Taken together, these results promote the use of P. luminescens TT01 as a potent bioinsecticide to control effectively A. segetum by oral treatment in a mixture with Vip3Aa16 toxin. Graphical abstract: Highlights: At 5 × 10 7  cells/ml, TT01 cells caused A. segetum mortality of 32.36%. TT01 cells oral toxicity is associated to septicaemia. Combination of TT01 cells and Bt Vip 3 toxin, resulted in 100% A. segetum mortality.